Improving Students’ Listening Skills Through Watching English Movie for Vocational High School - Masturoh, Khoirunnisa Hifjiah; Siahaan, Leroy Holman; Chairiyani, Ika (Innovative: Journal Of Social Science Research, 2024)
The study aimed to examine and explain how watching English-language films helped tenth-grade students at SMK Alam Karya Sukawangi Bekasi develop their listening abilities. The X OTKP class, which included 22 pupils, is the focus of this study. Classroom Action Research (CAR) is the methodology used in this study, in which the author works with an English instructor. The action research processes of Kemmis and McTaggart—planning, acting, observing, and reflecting—were followed in the conduct of this study. Cycles of the examination were conducted. Every cycle had between three and five meetings. The statistics gathered for this study came from the observation, interview, check, and teacher's logbook. The study's findings suggest that the students' listening proficiency has improved. At the end of the cycle, most students consistently achieved appropriate ranks. The English lesson's Minimum Mastery Criterion (KKM) score was 71.00. Ten students, or 45.45% of the student body, passed the KKM in the pre-test, with a mean score of 62.42. With a mean score of 67.22, 13 students, or 54.54%, have passed the KKM in cycle one, according to the results of post-test 1. Subsequently, the post-check 2 result from the second cycle shows that sixteen students, or 72.72%, passed the KKM with a mean score of 78.45. The English teacher and the students responded well to the activity, and the classroom environment during the teaching-learning process was good. In summary, pupils' listening abilities can be enhanced by watching English-language films.